Laboratory studies on the effects of transgenic corn on the spider mite Tetranychus urticae Koch (Bollettino di zoologia agraria e bachicoltura, 2024)
The possible influence of transgenic Event 176 com on the developmentof the mite Tetranychus urticae Koch was evaluated for the first and thesecond generation. Laboratory studies were carried out on transgenic and isogeniccom using this phytophagous mite, measuring the time of development of thedifferent stages, the survival of both sexes and the abundance of eggs laid andhatched. The results do not highlight significant differences between the parametersstudied.
Keywords: Bt com; Tetranychus urticae; non target species; side effects